Inhibition of Long Noncoding RNA Linc‐Pint by Hepatitis C Virus in Infected Hepatocytes Enhances Lipogenesis. Issue 1 (2nd May 2021) - Khatun, Mousumi; Sur, Subhayan; Steele, Robert; Ray, Ranjit; Ray, Ratna B.
Abstract : Background and Aims: HCV often causes chronic infection in liver, cirrhosis, and, in some instances, HCC. HCV encodes several factors' those impair host genes for establishment of chronic infection. The long noncoding RNAs (lncRNAs) display diverse effects on biological regulations. However, their role in virus replication and underlying diseases is poorly understood. In this study, we have shown that HCV exploits lncRNA long intergenic nonprotein‐coding RNA, p53 induced transcript (Linc‐Pint) in hepatocytes for enhancement of lipogenesis. Approach and Results: We identified a lncRNA, Linc‐Pint, which is significantly down‐regulated in HCV‐replicating hepatocytes and liver specimens from HCV infected patients. Using RNA pull‐down proteomics, we identified serine/arginine protein specific kinase 2 (SRPK2) as an interacting partner of Linc‐Pint. A subsequent study demonstrated that overexpression of Linc‐Pint inhibits the expression of lipogenesis‐related genes, such as fatty acid synthase and ATP‐citrate lyase. We also observed that Linc‐Pint significantly inhibits HCV replication. Furthermore, HCV‐mediated enhanced lipogenesis can be controlled by exogenous Linc‐Pint expression. Together, our results suggested that HCV‐mediated down‐regulation of Linc‐Pint enhances lipogenesis favoring virus replication and liver disease progression. Conclusions: We have shown that SRPK2 is a direct target of Linc‐Pint and that depletion of SRPK2 inhibits lipogenesis. Our study contributes to the mechanistic understanding of the role of Linc‐Pint in HCV‐associated liver pathogenesis.